Acute coronary syndromes in clinical practice - Bavry, Anthony Alexander; Bhatt, Deepak L. (Springer, 2019)
Acute coronary syndromes affect millions of individuals annually by causing considerable morbidity and mortality. In developed countries this disease remains the number one killer, despite significant improvements in its management over the last several decades. Acute coronary syndromes are challenging, as the field is a fast moving one with a rapid proliferation of drug and device trials. These new studies become incorporated into separate guideline recommendations by both American and European writing committees, which are frequently updated. Moreover, there are separate guideline recommendations for stable angina, non-ST-elevation acute coronary syndrome, ST-elevation myocardial infarction, and percutaneous coronary intervention. This may make it relatively difficult for practitioners to keep up-to-date with the field. Unfortunately, there is often a gap between the guideline recommendations and the care that is delivered in the 'real world'. In this book we have attempted to distil the considerable literature on this topic into an accurate, succinct and up-to-date review of acute coronary sindromes. Many specialties are involved in the diagnosis and management of these syndromes; therefore, our audience includes a variety of practitioners: cardiologists, general practitioners, emergency medicine physicians, nurses, nurse practitioners, nursing students, physician trainees, medical students, pharmacists, and paramedics. We take the reader through the epidemiology and prognosis, diagnosis and clinical manifestations, risk stratification, and percutaneous and medical therapies across the entire spectrum of acute coronary syndromes. We end with a discussion on current controversies and future approaches to the treatment of acute coronary syndromes.